Knowledge and Perception Of Pain About Diabetes Mellitus With Self Care Bahavior In Diabetes Mellitus Patients - Kholis Khoirul Huda; Tomy Suganda; Romy Suwahyu; Nurul Septiani (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2023)
Diabetes Mellitus is a chronic disease that requires long-term self-care so that patients can carry out self-care independently to prevent complications from Diabetes Mellitus. Self Care Behavior aims to examine and classify the extent to which people with Diabetes Mellitus carry out self-care in order to improve their well-being and quality of life. This study aims to determine the relationship between knowledge and pain perceptions about Diabetes Mellitus and Self Care Behavior of Diabetes Mellitus sufferers. This research is a literature study that summarizes some of the relevant literature collected using Google Scholar which was published in 2015-2022. The results of the search found 56 identified journals and 7 journals that met the inclusion criteria. The results showed that there was a significant relationship between knowledge about Diabetes Mellitus and Self Care for Diabetes Mellitus patients and there was a significant relationship between perceptions of pain about Diabetes Mellitus and self care behavior for Diabetes Mellitus sufferers.